Yield and nitrogen, nitrate and potassium content in the grain of pea using N, K, S in the greenhouse - Silva, José Joaquim Santana e; Bohnen, Humberto (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was conducted with the objective of evaluating the response of pea (Pisum sativum L.) cv. Triofin when growing in alfisol (Millic Ochraqualfs) with differents N (0 ppm, 50 ppm and 100 ppm), K (0 ppm, 100 ppm and 200 ppm) and S (0 ppm and 30 ppm) levels. Results indicated the nitrogen when associated with the potassium increased only potassium concentration in the grain and that potassium was the nutrient that increased more the yield and the protein nitrogen.